TYPES OF SCIENTIFIC DESCRIPTIONS IN ROMANIAN GEOGRAPHY TEXTBOOKS - BLÎNDA, VIORICA (Universitatea "Babeş-Bolyai" Cluj Napoca, 2018)
This study will provide a brief look into the numerous aspects of description as a unit of discourse and into the/as well as into those/distinctive discourse methods. The perspectives of the proposed analysis emphasize that description as a unit of discourse is no longer denigrated and that it has regained its well-defined place within the discourse (especially within the discourse of geography as a primary unit of discourse). The analysis is based on a corpus of studies represented by texts of geography available in geography textbooks. Through this study there will be outlined a number of methods and strategies of the discursive process through description.